One (un)like the other: rethinking ethics, empathy, and transcendence from Husserl to Derrida - Andrews, Michael F. (SUNY series in theology and continental thought, 2024)
"Aims to rethink ethics and transcendence in light of the phenomenology of empathy and social ontology"